2004
DOI: 10.3892/ijo.25.3.555
|View full text |Cite
|
Sign up to set email alerts
|

Diosgenin induces cell cycle arrest and apoptosis in HEL cells with increase in intracellular calcium level, activation of cPLA2 and COX-2 overexpression

Abstract: Many natural components of plant extracts are studied for their beneficial effects for health and particularly on carcinogenesis chemoprevention. In the present study, we investigated the effects of diosgenin on erythroleukemia HEL cells. Our results demonstrated that diosgenin induced G2/M arrest of cell cycle progression through p21 up-regulation in a p53-independent pathway and strong induction of apoptosis in HEL cells. Apoptosis induction was accompanied by an increase in Bax/Bcl-2 ratio, PARP cleavage an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 0 publications
3
44
0
Order By: Relevance
“…Particular attention has been given to their potential for cancer chemoprevention, especially as apoptosis inductors (25). Recently, we demonstrated that diosgenin-induced apoptosis in cancer cell lines (26)(27)(28). Furthermore, we described for the first time that diosgenin-induced apoptosis in human RA FLS with COX-2 overexpression (14).…”
Section: Discussionmentioning
confidence: 99%
“…Particular attention has been given to their potential for cancer chemoprevention, especially as apoptosis inductors (25). Recently, we demonstrated that diosgenin-induced apoptosis in cancer cell lines (26)(27)(28). Furthermore, we described for the first time that diosgenin-induced apoptosis in human RA FLS with COX-2 overexpression (14).…”
Section: Discussionmentioning
confidence: 99%
“…Extracts from these plants have been traditionally used for the treatment of diabetes (Madar et al, 1988;Sharma et al, 1990;Gupta et al, 2001), hypercholestrolemia (Valette et al, 1984;Sauvaire et al, 1991), and gastrointestinal ailments (Pandian et al, 2002;Raju et al, 2004). Research during the last decade has shown that diosgenin suppresses proliferation and induces apoptosis in cells of human colon carcinoma (Raju et al, 2004;Wang et al, 2004), osteosarcoma (Moalic et al, 2001;Corbiere et al, 2003), leukemia (Hibasami et al, 2003;Liu et al, 2005), human erythroleukemia (Leger et al, 2004), and human rheumatoid arthritis . Antiproliferative effects of diosgenin are mediated through cell cycle arrest (Moalic et al, 2001;Liu et al, 2005), disruption of Ca 2 þ homeostasis (Leger et al, 2004;Liu et al, 2005), the activation of p53, release of apoptosis-inducing factor, and modulation of caspase-3 activity .…”
Section: Introductionmentioning
confidence: 99%
“…Research during the last decade has shown that diosgenin suppresses proliferation and induces apoptosis in cells of human colon carcinoma (Raju et al, 2004;Wang et al, 2004), osteosarcoma (Moalic et al, 2001;Corbiere et al, 2003), leukemia (Hibasami et al, 2003;Liu et al, 2005), human erythroleukemia (Leger et al, 2004), and human rheumatoid arthritis . Antiproliferative effects of diosgenin are mediated through cell cycle arrest (Moalic et al, 2001;Liu et al, 2005), disruption of Ca 2 þ homeostasis (Leger et al, 2004;Liu et al, 2005), the activation of p53, release of apoptosis-inducing factor, and modulation of caspase-3 activity . It also inhibits azoxymethane-induced aberrant colon crypt foci (Raju et al, 2004) and has been shown to inhibit intestinal inflammation (Yamada et al, 1997) and modulate the activity of lipoxygenase (LOX) (Nappez et al, 1995) and cyclooxygenase-2 (COX-2) (Moalic et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…One of the most compounds that founded in fenugreek is Diosgenin with anticancer activity.The study effect of diosgenin on osteosarcoma cells were showed that diosgenin treatment caused an inhibition of 1547 cell growth with a cycle arrest in G1 phase and apoptosis induction and moreover exist a correlation between p53, p21 mRNA expression and nuclear factor-kappaB activation (Moalic et al, 2001). Diosgenin induces cell cycle arrest and apoptosis in HEL cells with increase in intracellular calcium level, activation of cPLA2 and COX-2 overexpression (Leger et al,2004). Another study about diosgenin effect on colon cancer cells showed that diosgenin induces death receptor-5 through activation of p38 pathway and promotes TRAIL-induced apoptosis (Lepage et al, 2011).…”
Section: Discussionmentioning
confidence: 99%